2019
DOI: 10.3390/molecules24152778
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Snake Venom Components—A Mini-Review

Abstract: Hypertension is considered a major public health issue due to its high prevalence and subsequent risk of cardiovascular and kidney diseases. Thus, the search for new antihypertensive compounds remains of great interest. Snake venoms provide an abundant source of lead molecules that affect the cardiovascular system, which makes them prominent from a pharmaceutical perspective. Such snake venom components include bradykinin potentiating peptides (proline-rich oligopeptides), natriuretic peptides, phospholipases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 115 publications
0
35
0
Order By: Relevance
“…Proline-rich peptides represent an important group of insect antimicrobial peptides 71 . Moreover, proline is the main constituent of hypotensive peptides (bradykinin potentiating peptides) occurring in snake venoms 72 . Villar-Briones and Aird 42 reported that proline and arginine are the most abundant free amino acids in snake venoms (Elapidae, Viperinae, and Crotalinae).…”
Section: Discussionmentioning
confidence: 99%
“…Proline-rich peptides represent an important group of insect antimicrobial peptides 71 . Moreover, proline is the main constituent of hypotensive peptides (bradykinin potentiating peptides) occurring in snake venoms 72 . Villar-Briones and Aird 42 reported that proline and arginine are the most abundant free amino acids in snake venoms (Elapidae, Viperinae, and Crotalinae).…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms and evolution are very similar to sepsis that induces decrease in systemic vascular resistance, increase in cardiac output and kidney vascular resistance which lead to a decrease in kidney blood flow and glomerular filtration rate. Many snake venom peptides and enzymes impact blood pressure regulation, peripheral vasomotricity, integrity of vascular endothelium and kidney sodium reabsorption [ 33 - 35 ]. Phospholipases A 2 (PLA2s) activate the metabolism of prostaglandins and leukotrienes which play a central role in the inflammatory response through the metabolic cascade of arachidonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Another important component of RAS that is often overlooked and in fact did not appear to be discussed (Covid-19 context) in any of the articles that we have reviewed is the bradykinin pathway (Marceau et al,2020). Bradykinin is a proinflammatory proliferative peptide hormone inducing vasodilation, vascular permeability and edema (Kempe et al,2020;Lopatko et al,2019;Pé terfi et al,2019). Bradykinin is upregulated by ACE inhibitors (Bakhle, 2020) and may be playing a significant role that has gone unnoticed in the Covid-19 saga.…”
Section: Background On the Renin-angiotensin System As It Pertains Tomentioning
confidence: 99%